Promotion Outdoor Hydroponic Vegetable Planting as a Source of Family Nutrition - A. Besse Dahliana; Jumardi; Hujemiati; Andi Rismayanti Fianda Sari; Darma; Hasmidar; Fitriadi (Jurnal Pengabdian Masyarakat Bestari, 2023)
Community service aims to 1) increase knowledge and skills and empower the community to manage the yard as a source of food security and family nutrition; and 2) apply simple hydroponic cultivation techniques in the yard and plant maintenance that is easily applied by the community. This community service is an effort to increase public knowledge about the use of yards through hydroponic vegetable cultivation techniques as a source of family nutrition. The community service method used is lectures, discussions, and practical activities in the field. The results of community service that have been carried out are as follows: 1) this counseling activity can add insight and knowledge to the community about the business of using yard land with hydroponic vegetable cultivation techniques as a source of family nutrition 2) the community, which is a group of housewives in Lampoko Village, has implemented the use of the yard with hydroponic vegetable cultivation techniques, so this activity is directed at increasing the skills of mothers to carry out hydroponic vegetable cultivation techniques